2015
DOI: 10.1159/000366209
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of 120 W Laser Photoselective Vaporization versus Transurethral Resection of the Prostate for Bladder Outlet Obstruction by Prostate Cancer

Abstract: Objective: To compare the mid-term outcomes of photoselective vaporization of prostate (PVP) with GreenLight HPS 120 W laser and transurethral resection of the prostate (TURP) for obstructive lower urinary tract symptoms (LUTS) in men with prostate cancer (CaP). Patients and Methods: Seventy four patients with locally advanced (T3/T4) CaP with severe LUTS or acute urinary retention (AUR) were allocated to TURP (n = 36) or PVP (n = 38). International Prostate Symptom Scores (IPSS), maximum flow rates (Qmax) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Therefore, in recent years, new procedures have been developed in order to guarantee reduced morbidity, reduced catheterization time and hospitalization. Recent literature has shown that laser surgery, by means of Green Light photoselective vaporization, Holmium laser enucleation of the prostate (HoLEP) and Thulium laser enucleation of the prostate (ThuLEP) is considered an effective surgical alternative [4,5,6,7]. The purpose of this study is to test the andrological impact of ThuLEP in terms of erectile and ejaculatory functions, on lower urinary tract symptoms (LUTS) modifications and on improvements of QoL.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in recent years, new procedures have been developed in order to guarantee reduced morbidity, reduced catheterization time and hospitalization. Recent literature has shown that laser surgery, by means of Green Light photoselective vaporization, Holmium laser enucleation of the prostate (HoLEP) and Thulium laser enucleation of the prostate (ThuLEP) is considered an effective surgical alternative [4,5,6,7]. The purpose of this study is to test the andrological impact of ThuLEP in terms of erectile and ejaculatory functions, on lower urinary tract symptoms (LUTS) modifications and on improvements of QoL.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Liberale et al [26] presented their experience with PVP in 43 patients with prostate cancer and showed that for patients with prostate cancer, PVP is safe and provides excellent relief from symptoms. Altay et al [27] compared PVP and TURP for bladder outlet obstruction by locally advanced (cT3/T4) prostate cancer. In their study, there were no significant differences in adverse events and primary functional outcomes between the 2 groups of 34 patients who underwent TURP and 35 patients who underwent PVP and completed 12 months of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…We also acknowledged that our management of patients with elevated PSA level (ie, prostate biopsy during PVP) could be questionable, as one can argue that diagnosing prostate cancer preoperatively would be preferable and could have changed the management of No Complication n ¼ 132 (86.9) Acute urinary retention due to clusters of necrotic deposits removed at fibroscopy or cystoscopy n ¼ 3 (2) Clusters of necrotic deposits requiring a new resection n ¼ 2 (1.3) Erectile dysfunction n ¼ 2 (1.3) Uretral stenosis n ¼ 2 (1.3) Urgency with sterile urine culture not treated n ¼ 1 (0.6) Urgency with sterile urine culture treated by antimuscarinic or non steroid anti-inflammatory n ¼ 1 (0.6) Urinary incontinence not requiring pads n ¼ 6 (4) Urinary incontinence requiring at least 1 pad n ¼ 3 (2) these patients. However, several series have recently assessed the reliability of PVP in patients with prostate cancer, 18,19 and to our knowledge, the appropriate timing to perform prostate biopsy in the setting of PVP has not been addressed in current guidelines. Another potential limitation is that 3 different types of fibers were used (XPS, HPS, KTP-80W), which could have biased the results observed as it has been hypothesized that the higher energy application and higher speed of tissue vaporization with the XPS fiber could lead to increased tissue vaporization compared with the former 120-W and 80-W laser systems.…”
Section: Commentmentioning
confidence: 99%